Tax Avoidance Analysis in Healthcare Companies - Rizky Khaerany; Haliah; Nirwana (Westscience Press, 2024)
The study aims to analyze the impact of profitability, liquidity, and leverage on tax avoidance practices carried out on health sector companies listed on the Indonesian Stock Exchange. The research method used is descriptive. The data analysis technique used is double regression analysis using purposive sampling so that the number of samples used is 15 companies listed on the Indonesia Stock Exchange in the period 2020-2022. The results of the study indicate that partially, profitability and liquidity have no influence on tax avoidance practices. The variable that influences tax avoidance based on this study is leverage. Simultaneously the three variables have an influence on the company's decision to conduct tax avoidance practices.